PERANCANGAN MODUL NOTIFIKASI OTOMATIS PADA APLIKASI NEVIRA SEBAGAI POINT OF SALE USAHA LAUNDRY MENGGUNAKAN METODE SCRUM - Wildan Suharso; hafizh (LPPM Universitas Abdurrab, 2026)
The Nevira application is a web-based laundry business information system developed to support operational management, particularly transaction recording, service-progress monitoring, and information delivery to users. The main problem addressed is the absence of an automatic and real-time mechanism for communicating service-status information, which causes communication delays (a communication gap) between operational staff and the business owner. This study aims to develop an automatic notification module integrated into the Nevira system to convey service-status changes quickly and accurately. The development method used is Scrum, an iterative and incremental approach carried out through six two-week sprints, with product-backlog prioritization performed using the Eisenhower Matrix. Functional testing was conducted using Black Box Testing with the Equivalence Partitioning technique and complemented by User Acceptance Testing (UAT). The testing results show that all test scenarios (18 test cases executed on the Back Office and Point of Sale platforms) were valid/passed, while the UAT obtained a 100% acceptance rate from the primary user (the business owner). Therefore, applying the Scrum method in development and the Equivalence Partitioning technique in testing is proven capable of producing a functional, efficient automatic notification module that meets user needs.